The Effects of Duolingo, an AI-Integrated Technology, on EFL Learners’ Willingness to Communicate and Engagement in Online Classes - Ouyang, Zhiqun; Jiang, Yujun; Liu, Huying (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2024)
This study, which is quasi-experimental in nature, looks into how language learners’ willingness to communicate and engagement in English as a foreign language (EFL) classrooms are affected by Duolingo. The control and experimental groups comprised two complete classes with forty EFL students. To compare learner engagement and communication willingness scores before and after treatment, the study used independent samples t-tests. The results demonstrated the groups’ initial homogeneity by showing no discernible differences prior to the intervention. The results confirmed the effects on learner engagement, which showed significant gains in affective, cognitive, and behavioral domains, indicating Duolingo’s beneficial impact on engagement in general. Furthermore, the significant effect sizes observed confirmed Duolingo’s contribution to improved language attitudes, engagement, and communicative confidence. Compared to the control group, the experimental group’s willingness to speak, read, write, comprehend, and communicate generally improved in a manner that was statistically significant. The significant effect sizes demonstrate how well Duolingo works to improve different aspects of willingness to share. The study emphasizes the pedagogical tool’s adaptability and encourages teachers to integrate Duolingo for a comprehensive and technologically enhanced language learning experience. Practical implications arise for EFL teachers who use online learning resources.